2018
DOI: 10.1101/323576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-assembly, quality evaluation, and annotation of 678 microbial eukaryotic reference transcriptomes

Abstract: Background De novo transcriptome assemblies are required prior to analyzing RNAseq data from a species without an existing reference genome or transcriptome. Despite the prevalence of transcriptomic studies, the e ects of using di erent work ows, or "pipelines", on the resulting assemblies are poorly understood. Here, a pipeline was programmatically automated and used to assemble and annotate raw transcriptomic short read data collected by the Marine Microbial Eukaryotic Transcriptome Sequencing Project (MMETS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…Dinoflagellate transcripts were then aligned to Brandtodinium nutricula RCC 3387 (MMETSP1462) transcriptome assembly (Johnson et al, 2018) with BLASTN using a 90% identity cutoff and 50% coverage cutoff for the shorter sequence. Transcripts aligned to the B. nutricula transcriptome were considered Brandtodinium sequences.…”
Section: Assembly and Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinoflagellate transcripts were then aligned to Brandtodinium nutricula RCC 3387 (MMETSP1462) transcriptome assembly (Johnson et al, 2018) with BLASTN using a 90% identity cutoff and 50% coverage cutoff for the shorter sequence. Transcripts aligned to the B. nutricula transcriptome were considered Brandtodinium sequences.…”
Section: Assembly and Annotationmentioning
confidence: 99%
“…Original reads of the B. nutricula RCC3387 (MMETSP1462) transcriptome were downloaded from iMicrobe 1 . Its transcriptome assembly were downloaded from Johnson et al (2018). The same pipeline of read alignment, read count generation, rRNA/chloroplast/mitochondria sequence identification, protein prediction and annotation described above was also applied to the MMETSP1462 transcriptome.…”
Section: Comparison With B Nutricula Transcriptomementioning
confidence: 99%
“…The stringency for quality trimming of RNA-seq libraries prior to assembly plays a role in determining the number of unique contigs recovered and the subsequent assembly quality of transcriptomes. Regarding the transcriptome assembly method, Johnson et al (2018) evaluated the publicly available assemblies from MMETSP using BUSCO scores, compared to processing and re-assembly with Trinity (Johnson et al, 2018). Johnson et al (2018) demonstrated that while the raw data available from the MMETSP project is an excellent resource, the assemblies available as part of the project are of a lower quality than what can be achieved with current methods (Johnson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…High stringency is usually favored, however MacManes (2014) found that this can be detrimental to the assembly and the quality cut off scores used in the present study were based on those recommendations (MacManes, 2014). In short, the trimming and assembly pipeline used for the assemblies available as part of MMETSP is no longer state-of-the-art and this is reflected in the quality comparison conducted by Johnson et al (2018). To address this problem, we developed a workflow implementation of current best-practice transcriptome assembly methods as part of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis and related mustards have five phytochromes, but one of these (PHYD) is a late duplication found only in the flowering plant family Brassicaceae (Mathews, ; Mathews & McBreen, ). The model kelp Ectocarpus siliculosus has four phytochromes (Cock et al , ), as do some Hemiselmis strains (Keeling et al , ; Johnson et al , ). Remarkably, phytochrome gene families have apparently undergone much greater expansion in glaucophytes, with as many as 11 members of this family in Cyanophora paradoxa (Price et al , ).…”
Section: Duplication: Many Phytochromes From Onementioning
confidence: 99%